Would you rather? Household choice between cash transfers or an economic inclusion program - Allen IV, James; Gilligan, Daniel O.; Kurdi, Sikandra; Yassa, Basma (International Food Policy Research Institute, 2024)
We study households’ choice between continued cash transfers and a new economic inclusion program—two global prevalent social protection programs—offered by the Egyptian government. Lower-than-expected early adoption of the new program is correlated with differing perceptions on its design. We randomize official messaging to households describing the new program’s (i) consumption support duration and (ii) income-earning potential. Both treatments increase respondents’ likelihood of recommending the new program. A theoretical model estimated using households’ perceptions of program design predicts interest in the new program, and how it diminishes with increasing effort costs, asset loss probability, risk aversion and loss aversion.